Animowanie teorii .......... 23 - Korporowicz, Leszek (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
ANIMATION OF THEORY The article discusses efforts to build a theory of intercultural relations as a relatively autonomous and integrated field of reflection, showing both past and present achievements. Of particular interest within the article is the fundamental contribution of Tadeusz Paleczny as the doyen of works creating the systematics and methodology of intercultural studies, creating a rule for the integration of threads undertaken on the basis of many scientific disciplines, comparing key categories of analysis and outlining important contexts of both contemporary and future research. At the same time, the text proposes a closer analysis of particularly important theoretical and practical implications directly resulting from the area of reflection on the phenomenon of interculturality, such as intercultural rights, communication, education and intercultural space, along with the problem of intercultural heritage, which is important for the contemporary world.